A strategic financial plan for Alpha Insurance & Surety Co., Inc - Buillery, Michael Raphael L.; Gonzales, Jade Kristoffer Z.; Sayde, Joan M.; Cortez, Abigael C.; Bacsa, Ciara Diorelle G.; Bonifacio, Tristine P.; Capupus, Cae Ronisia P.; Galon, Rica Mae T.; Lorenzo, Raniel C.; Magat, Jillian C.; Reyes, Jane Honey B. and Sison, Crisanto M. (Manila: PLM, 2019)
EXECUTIVE SUMMARY: Alpha Insurance & Surety Co., Inc. is a domestic non-life insurance provider established on May 13, 1957. It is a 100% Filipino-owned corporation which is composed of 280 employees and more than 200 agents and intermediaries as of 2017. It seeks to lead, promte, and sustain excellence in providing comprehensive e non-life insurance services to the insuring public. Together with its shareholders, the entity adheres the time-honored values of trust, commitment, and integrity in providing the utmost products and services to suit the ever-changing needs of the Filipinos. This report provides an analysis on the financial operations of the entity for the past six years using its audited financial statements for the years 2012-2017; and through company interview. Comprehensive assessment on its performance reveals that the entity has been performing well as to its solvency ratios, However, it was also revealed that the entity is having difficulty in maintaining an optimal level of liquidity, as evident in its difficulty in covering for claims and in collecting its receivables. To address these problems, this paper provides detailed courses of action. The best alternative course of action of pursuing additional payment options thru mobile wallet, online banking, and remittance center was identified. In pursuing this, the clients may settle their accounts conveniently while increasing the actual collections of the entity. This paper also includes the projected financial condition of the entity for the next five years after the implementation of the chosen course of action.
EXECUTIVE SUMMARY: Alpha Insurance & Surety Co., Inc. is a domestic non-life insurance provider established on May 13, 1957. It is a 100% Filipino-owned corporation which is composed of 280 employees and more than 200 agents and intermediaries as of 2017. It seeks to lead, promte, and sustain excellence in providing comprehensive e non-life insurance services to the insuring public. Together with its shareholders, the entity adheres the time-honored values of trust, commitment, and integrity in providing the utmost products and services to suit the ever-changing needs of the Filipinos. This report provides an analysis on the financial operations of the entity for the past six years using its audited financial statements for the years 2012-2017; and through company interview. Comprehensive assessment on its performance reveals that the entity has been performing well as to its solvency ratios, However, it was also revealed that the entity is having difficulty in maintaining an optimal level of liquidity, as evident in its difficulty in covering for claims and in collecting its receivables. To address these problems, this paper provides detailed courses of action. The best alternative course of action of pursuing additional payment options thru mobile wallet, online banking, and remittance center was identified. In pursuing this, the clients may settle their accounts conveniently while increasing the actual collections of the entity. This paper also includes the projected financial condition of the entity for the next five years after the implementation of the chosen course of action.
F
Keywords: academic writing